Injectable uncrosslinked biomimetic hydrogels as candidate scaffolds for neural stem cell delivery. Issue 3 (18th November 2016) - Farrell, Kurt; Joshi, Jyotsna; Kothapalli, Chandrasekhar R.
Abstract: Mammalian central nervous system has a limited ability for self‐repair under diseased or injury conditions. Repair strategies focused on exogenously delivering autologous neural stem cells (NSCs) to replace lost neuronal populations and axonal pathways in situ, and promote endogenous repair mechanisms are gaining traction. Successful outcomes are contingent on selecting an appropriate delivery vehicle for injecting cells that promotes cell retention and survival, elicits differentiation to desired lineages, and enhances axonal outgrowth upon integration into the host tissue. Hydrogels made of varying compositions of collagen, laminin, hyaluronic acid (HA), and chondroitin sulfate proteoglycan (CSPG) were developed, with no external crosslinking agents, to mimic the native extracellular matrix composition. The physical (porosity, pore‐size, gel integrity, swelling ratio, and enzymatic degradation), mechanical (viscosity, storage and loss moduli, Young's modulus, creep, and stress‐relaxation), and biological (cell survival, differentiation, neurite outgrowth, and integrin expression) characteristics of these hydrogels were assessed. These hydrogels exhibited excellent injectability, retained gel integrity, and matched the mechanical moduli of native brain tissue, possibly due to natural collagen fibril polymerization and physical‐crosslinking between HA molecules and collagen fibrils. Depending on the composition, these hydrogels promoted cell survival, neural differentiation, and neurite outgrowth, as evident from immunostaining and western blots. These cellular outcomes were facilitated by cellular binding via α6, β1, and CD44 surface integrins to these hydrogels. Results attest to the utility of uncrosslinked, ECM‐mimicking hydrogels to deliver NSCs for tissue engineering and regenerative medicine applications. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 790–805, 2017.